Manajemen Kepala Sekolah Dalam Meningkatkan Kompetensi Guru di SMP Negeri 21 Bandar Lampung Tahun Pelajaran 2023/2024 - Tanti Prihartini (Pusat Riset dan Inovasi Nasional, 2024)
Competency standards are a breakthrough in the world of education in improving the quality of teachers so as to make teachers not only professional but competent in their fields. This is an implementation of the national education system law, the national standard of education (SNP), the Teacher and Lecturer Law (UUGD), which is realized in the RPP on teachers which will soon be passed. Departing from the above thinking, the author takes the title